Light Impacts Mg Incorporation in the Benthic Foraminifer Amphistegina lessonii - Dämmer, Linda K.; de Nooijer, Lennart J.; Reichart, Gert-Jan (Frontiers in Marine Science, 2019)
The ratio of Mg to Ca in foraminiferal calcium carbonate (Mg/Cacc) is a popular tool to reconstruct past sea water temperatures. Its application is being complicated by other environmental factors affecting the Mg/Cacc, including salinity and the ratio between sea water [Mg2+] and [Ca2+]. Furthermore, there is considerable intra-specimen variability in Mg/Ca in the form of alternating high- and low-concentration bands. This banding has recently been linked to diurnal cyclicity, in which bands with relatively high Mg/Ca are precipitated during night time. Here we show that light not only impacts variability due to banding but also significantly affects average chamber Mg/Ca in the large benthic, symbiont-bearing foraminifer Amphistegina lessonii. These ratios are higher in foraminifera that calcify for a longer time in the dark, with a difference in Mg/Ca of 23 mmol/mol between carbonate formed completely in the dark versus completely in the light. We propose that individual timing of chamber formation and thus presence or absence of light during calcification is an important driver of inter-specimen variability in foraminiferal Mg/Ca.